A mechanism for electrostatic solitary structures in the Earth's magnetosheath - Lakhina, G. S.; Singh, S. V.; Kakad, Amar; Goldstein, M. L.; Viñas, A. F.; Pickett, J. S. (My University, 2009)
Electrostatic solitary waves (ESWs) have been observed in the Earth's magnetosheath region by Cluster. A mechanism for the generation of these structures in terms of electron-acoustic solitons and double layers is discussed. The model simulates the magnetosheath plasma by a four-component plasma system consisting of core electrons, two counterstreaming electron beams, and one type of ions. The analysis is based on the fluid equations and the Poisson equation, and employs the Sagdeev pseudopotential techniques to investigate the solitary waves. The electric field amplitudes, the time durations, and the propagation speeds of the solitary structures predicted by the model are in good agreement with the observed electric fields, pulse widths, and speeds of the electrostatic bipolar pulses.
Keywords: Earth's magnetosheath; Electrostatic solitary waves; Solitary waves; Solitary structures